Kontribusi Fasilitas, Kompetensi Pengelola Dan Manajemen Laboratorium Terhadap Efektifitas Pembelajaran Ipa Di Smp Batik Surakarta Tahun Pelajaran 2015/2016 - Sulistyanto, Danang, Dr. Sumardi, M.Si, Dr. Suyatmini, M.Si (2017)
The purpose of this study there are four, the first test and analyze the contribution of facility, management competence, and the laboratory management for the effectiveness of learning science , second, test and analyze the contribution of facility to the effectiveness of learning science, third, test and analyze the contribution of management competence to the effectiveness of learning science , the fourth test and analyze the contribution of the laboratory management to the effectiveness of learning science Quantitative research, research design ex-post facto by the correlation technique. Research conducted at Batik Junior School of Surakarta in the second semester of the school year 2015/2016 with a sample of 125 students. The sampling technique using proportional random sampling using . Data collection techniques in this study using questionnaires and observation. Data analysis techniques used in this research is multiple regression analysis after classical assumption test such as the test for normality, linearity test, autocorrelation test, and test multicollinearity. The results of the study there were four, (1) there are contribution of facility, management competence, and the laboratory management in a significant 0.05 on the effectiveness of learning science was 29,246%, (2) there is a contributions facility at 0.05 significant to the effectiveness of learning science and contribute effectively amounted to 9,725 %, (3) there is a significant contribution of management competence 0,05 to the effectiveness of learning science and contribute effectively amounted to 9.898 %, (4) there is a significant contribution to the laboratory management 0.05 to the effectiveness of learning science and contribute effectively 9,623 %.